New hexanuclear FeIII clusters with the gem-diol hydrated form of di(2-pyridyl)ketone and carboxylato ligands: Crystal structures and magnetic properties. (1st December 2019) - Arizaga, Livia; Cañon-Mancisidor, Walter; Gancheff, Jorge S.; Burrow, Robert A.; Armentano, Donatella; Lloret, Francesc; González, Ricardo; Kremer, Carlos; Chiozzone, Raúl
Graphical abstract: Two new hexanuclear complexes [Fe6 O2 Cl2 {(py)2 CO2 }2 (pyOH)2 (pyCOO)2 (Bu t COO)6 ] and [Fe6 O2 {(py)2 CO2 }2 (pyCOO)4 (Bu t COO)6 ] were obtained from [Fe3 O(Bu t COO)6 (H2 O)3 ] + in the presence of di(2-pyridyl)ketone in MeCN. Antiferromagnetic couplings between iron(III) ions lead to an S = 0 ground state in both compounds. Abstract: The hexanuclear compounds [Fe6 O2 Cl2 {(py)2 CO2 }2 (pyOH)2 (pyCOO)2 (Bu t COO)6 ] (1 ) and [Fe6 O2 {(py)2 CO2 }2 (pyCOO)4 (Bu t COO)6 ] (2 ) were obtained by condensation of the trinuclear μ3 -oxo-centered iron(III) pivalate [Fe3 O(Bu t COO)6 (H2 O)3 ] + in the presence of di(2-pyridyl)ketone [(py)2 CO] in MeCN at ambient temperature. Both complexes contain an analogous core which can be described as two Fe3 O 7+ units joined by gem-diolato (py)2 CO2 2− bridges. Variable-temperature magnetic susceptibility measurements in polycrystalline samples of 1 and 2 reveal strong antiferromagnetic couplings between the iron(III) ions leading to S = 0 ground states.